SIAKAD Revitalization: The Latest Solution in Answering the Challenges of Digitizing Education - Safrizal; Muhammad Agha Afkar (International Journal Software Engineering and Computer Science (IJSECS), 2023)
The use of SIAKAD in academic management at tertiary institutions has been investigated in previous research. While it has been shown to provide significant benefits in improving the efficiency and effectiveness of academic administration, there are still some challenges that need to be addressed, such as technical issues, lack of management support, and the need for training and technical support for SIAKAD users. Therefore, efforts are needed to improve adequate management and technological support in the development and implementation of SIAKAD in higher education institutions. In this article, the importance of revitalizing SIAKAD in facing the challenges of digitizing education is discussed. The current SIAKAD is not enough to face these challenges, so the revitalization of SIAKAD is necessary to accommodate user needs in the digital era. The latest solutions that can be implemented in the revitalization of SIAKAD are also described. These solutions include the use of cloud technology, artificial intelligence, and big data analytics, as well as integration with other systems such as e-learning and mobile apps. Through the revitalization of SIAKAD, higher education institutions can better respond to the challenges of digitizing education. A more effective and efficient SIAKAD can make the academic administration process easier and faster. Moreover, it can also improve the quality of academic services provided to students and lecturers. The article concludes by highlighting the importance of collaborative discussion and action between the management of higher education institutions, lecturers, and staff to improve the benefits of SIAKAD in academic administration and overall academic service quality in higher education institutions